Prevalence of carbohydrate metabolism disorders and association with cardiovascular diseases in a large Siberian region - V. V. Shabalin; Yu. I. Grinshtein; R. R. Ruf; I. V. Filonenko; S. A. Shalnova; O. M. Drapkina (Российский кардиологический журнал, 2022)
Aim. To study the prevalence of carbohydrate metabolism disorders in a repre - sentative sample of the working-age population of the Krasnoyarsk Krai aged 25-64 years and to identify the association of these disorders with cardiovascular pathology.Material and methods. A random representative sample within the all-Russian epidemiological study ESSE-RF included 1603 residents of the Krasnoyarsk Krai aged 25 to 64 years. The gradation of carbohydrate metabolism disorders was carried out on the basis of fasting plasma glucose level in accordance with the criteria of the American Diabetes Association (ADA). Hypertension (HTN) was defined as office BP ≥140/90 mm Hg or an indication of previous use of antihypertensive drugs. The presence of myocardial infarction (MI), stroke, coronary artery disease (CAD) was detected by anamnesis collection. Statistical processing was carried out using IBM SPSS v 22 and Microsoft Excel 2021 programs. When comparing differences by sex, age, level of education, and type of residence, differences was assessed by chi-squared test and considered significant at p≤0,05.Results. In total representative sample of Krasnoyarsk Krai population, 3,6% of participants indicated prior diabetes, while its prevalence naturally increased with age. The detection rate of fasting glucose of 5,6-6,9 mmol/l among individuals without prior diabetes (impaired fasting glycemia (IFG), as one of the criteria for prediabetes, according to ADA guidelines) was 22,5% of the general population. Fasting hyperglycemia (HG) ≥7,0 mmol/l without prior diabetes was registered in 3,8%. This figure can be roughly considered as the proportion of people with newly diagnosed diabetes. IFG and HG were significantly more common among men, as well as among those with primary and secondary education compared with higher education. In rural residents, all types of carbohydrate metabolism disorders were more common than in urban ones. Compared with the normoglycemic group, the presence of prior diabetes, IFG and GH was associated with a significantly higher prevalence of hypertension, CAD and stroke.Conclusion. The prevalence of IFG, fasting HG ≥7,0 mmol/l and diagnosed diabetes in a representative sample of the Krasnoyarsk Krai aged 25-64 years exceeds the national average, although it is consistent with the data of a number of other Siberian regions. The prevalence of both carbohydrate metabolism disorders in general and the percentage of possible undiagnosed diabetes increases with age. At the same time, there are more such individuals among those with primary and secondary education, as well as among rural residents. The approximate proportion of undiagnosed diabetes in the study population reaches 50%. Timely detection of carbohydrate metabolism disorders can contribute to the earlier implementation of active preventive measures and reduce the risk of cardiovascular events.